2013
DOI: 10.2146/ajhp130252
|View full text |Cite
|
Sign up to set email alerts
|

Medication-use evaluation with a Web application

Abstract: The MUET application has enabled the increased standardization of medication safety initiatives across the VA system and may serve as a useful model for the development of pharmacovigilance tools by other large integrated health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…A) and provided feedback to the majority of sites that volunteered to participate. ( ) We observed that 40%‐50% of all identified patients receiving anti‐CD20 Ab treatment in June to August 2016 did not have pretreatment HBV testing completed. Among patients with chronic or prior HBV requiring HBV antiviral prophylaxis, up to 40% of patients did not receive antiviral prophylaxis within 1 month of initiating anti‐CD20 Ab therapy.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…A) and provided feedback to the majority of sites that volunteered to participate. ( ) We observed that 40%‐50% of all identified patients receiving anti‐CD20 Ab treatment in June to August 2016 did not have pretreatment HBV testing completed. Among patients with chronic or prior HBV requiring HBV antiviral prophylaxis, up to 40% of patients did not receive antiviral prophylaxis within 1 month of initiating anti‐CD20 Ab therapy.…”
Section: Resultsmentioning
confidence: 83%
“…This analysis is limited by use of observational data, which do not prove causality. Earlier demonstrated to enhance laboratory testing and safe VHA medication use, ( ) the MUET currently identifies omissions of HBV testing and antiviral prophylaxis among all those identified as initiating anti‐CD20 Ab therapy and provides voluntary feedback to sites. As pretreatment HBV testing remains incomplete, our analyses required use of an estimation of 11% of patients with chronic or prior HBV (as observed in an earlier national VHA analysis ( ) ) to determine rates of HBV antiviral prophylaxis; the true numbers may differ slightly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MUET is a web-based application that provides VA medical centers with secured lists of target patients that meet pre-set criteria for intervention and enables the interventions to be "reported back" into a centralized database. 9 As examples, use of MUET improved prescribing of erythropoiesis-stimulating agents and enhanced compliance with the direct oral anticoagulant CFU. Risk reduction projects employ a variety of methods to improve medication use.…”
Section: Risk Reduction Projects and Medication Use Evaluationmentioning
confidence: 99%